Physical Hydraulics Model And Computational Fluid Dynamics Of Sg. Belibis Pump Sump - Wahab, Muhammad Khairi (2017)
Pump sump are widely used for various applications like irrigation, electric cooling tower and water supply. Improving performance in sump is needed to prolong the lifespan of a pump due to high maintenance costs, vibration and cavitation that affected by uneven flow, air entrainment, pre swirl and vortices. This research aims to study of the physical modelling and a commercial computational fluid dynamic (CFD) as a design optimization tool for pump sump. Unacceptable flow characteristics for instance are free surface vortex and sub subsurface vortex and swirl in the pump sump physical model are identified in physical modelling tests. Based on the concerns stated, the method of mitigation are taking into consideration in order to improve the hydraulic performance in pump sump. The block buffer wall was proposed in this reasearch. A simulation model of sump intake have been developed and validated the numerical simulation software by FLUENT ™ 6.2 software. Experimental and numerical study of hydraulic model investigates the flow characteristics in the pump sump. The model features four pumps (7.91 L/s for all pumps) with a total of 12 cases of study were analyzed and determined. Different values of water level (1.8m, 0.2m, and 0.30m) and pump flow rate (15L/s, 20L/s, and 25L/s) were conducted. Velocity measurements at the dividing cross section were obtained by an Acoustic Doppler Velocimeter (ADV), pump flow rate by flow meter (Dyna Handheld Transit Time Ultrasonic Flow Meters) and swirl angle in the suction intakes were measured by a vortimeter. The application of block buffer wall show an excellent feedback as it gave a better flow distribution in the sump. The formation on surface vortex are reduced from in range Type 4 to 5 to surface vortex in range Type 1 to 2 compared to wall fillet and floor splitter used. Furthermore, swirl angle for block buffer wall are reduced from12.4 ˚ to 2.8˚ compared to without block buffer wall. The relative error between experimental and CFD showed acceptable results with the higher value for case 3 is 20.3%, Case 6 is 13.1%, and Case 9 is 11.8%. Therefore the results considered acceptable in range less than 30%. Hence, this means CFD can be used as tool for predicting, designing and analysing for turbulence case. As parts of the objective in this reasearch was to propose modifications to reduce or eliminate the flow unacceptable, buffer block wall showing good effect as other modifications.